2021
DOI: 10.1002/jor.25101
|View full text |Cite
|
Sign up to set email alerts
|

Identification and coregulation pattern analysis of long noncoding RNAs following subacute spinal cord injury

Abstract: Long noncoding RNAs (lncRNAs) have been demonstrated to play critical regulatory roles in posttranscriptional and transcriptional regulation in eukaryotic cells.However, the characteristics of many lncRNAs, particularly their expression patterns in the lesion epicenter of spinal tissues following subacute spinal cord injury (SCI), remain unclear. In this study, we determined the expression profiles of lncRNAs in the lesion epicenter of spinal tissues after traumatic SCI and predicted latent regulatory networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…After larval infection, brain tissues were collected at 1, 7, 14, and 21 days, fixed in 4% paraformaldehyde, embedded in paraffin, dewaxed in xylene, immersed in different concentrations of ethanol and stained with H&E. Pathological changes in the brains of infected mice at different infection times were observed through H&E staining. After H&E staining, the nuclei were stained blue, and the cytoplasm was stained pink [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…After larval infection, brain tissues were collected at 1, 7, 14, and 21 days, fixed in 4% paraformaldehyde, embedded in paraffin, dewaxed in xylene, immersed in different concentrations of ethanol and stained with H&E. Pathological changes in the brains of infected mice at different infection times were observed through H&E staining. After H&E staining, the nuclei were stained blue, and the cytoplasm was stained pink [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 230 DE LncRNAs were identified, of which 172 were up-regulated and 58 were down-regulated [21]. The authors also constructed a ceRNA network to predict the targeting relationship between LncRNAs and miRNAs, which facilitates the screening of novel biomarkers that is critical in the molecular mechanism of SCI [21]. Duran RNA sequencing in the subacute and chronic stages of SCI [22].…”
Section: Changes Of Lncrnas After Spinal Cord Injurymentioning
confidence: 99%
“…Similarly, the authors reported a ceRNA network of LncRNAs-miRNAs-mRNAs interactions, including 655 nodes and 10,564 edges, in which LncRNA 1700020I14Rik, LncRNA Neat1, Lnc RNAXist and LncRNA Malat1 were identified to play a crucial part in regulating biological signaling pathways in SCI by interacting with other types of RNAs [ 20 ]. In another study, Wenzhao et al identified the expression profiles of LncRNAs after the subacute stage of SCI [ 21 ]. High-throughput sequencing were performed to identify DE LncRNAs, miRNAs and mRNAs in SCI at the transcriptome level, and the results were validated by qRT-PCR [ 21 ].…”
Section: Changes Of Lncrnas After Spinal Cord Injurymentioning
confidence: 99%
See 2 more Smart Citations